Społeczne i kulturowe aspekty grywalizacji w dobie pandemii = Social and cultural aspects of gamification during the pandemic era - Kleszczyński, Kamil (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article looks at the impact of the COVID-19 pandemic on the development of gamification. The pandemic has brought about a significant increase in digitisation, which is closely related to gamification. Moreover,as some proponents of gamification point out, its particular value comes from simplifying a complex reality. All of these make the pandemic seemlike a perfect breeding ground for the development of gamification. The author attempts to assess whether this is in fact the case by analysing various manifestations of gamification, especially in such areas as: media and communication, remote forms of work and learning, as well as controlling social behaviour.
Keywords: grywalizacja; pandemia; COVID-19; cyfryzacja; System Zaufania Społecznego; gamification; pandemic; digitalization; Social Credit System